Процессы в RLC-цепи синусоидального напряжения с управляемым реверсированием емкости - Шидловская, Н.А. (Технічна електродинаміка, 2011)
The processes in RLC-circuit, fed by a source of sinusoidal voltage, in which a capacitive element is reversed by controlled rectifiers are analysed. The recurrence formulas were obtained to find the voltage on capacity and current through the inductance after any quantity of reversed capacity. The main modes of circuit operation (oscillatory, limiting, aperiodic) as well as different variants of correlations between interval sizes after even and odd switching are considered. Diagrams which represent the processes in specific circuits are shown.